Sex difference in mouse metabolic response to erythropoietin - Zhang, Yuanyuan (FASEB J, 2017)
Erythropoietin (EPO) is the cytokine that regulates red blood cell production. Less understood is the nonerythroid action of EPO, including metabolic regulation of fat accumulation and glucose homeostasis. Although EPO treatment increased hematocrit and improved glucose tolerance in male and female mice, we observed a gender difference in EPO effects in weight control. EPO treatment reduced diet-induced weight gain from 9.6 ± 1.5 to 4.2 ± 1.4 g in male mice (P < 0.001), while the weight gain in female mice was similar (4.7 ± 2.0 g with PBS treatment and 3.3 ± 2.1 g with EPO treatment). EPO treatment also reduced weight gain in ovariectomized female mice, while the effect was abrogated with estradiol supplementation, suggesting that the sex-differential response to EPO was associated with estrogen. Furthermore, mice with targeted deletion of EPO receptor in white adipose tissue exhibited sex-differential phenotype in weight control and glucose sensitivity, and EPO receptor gene expression was reduced in wild-type female mice, suggesting that white adipose tissue plays an integral role in mediating the metabolic effects of EPO. Our data provide evidence for a sex-differential response to EPO in weight control in mice and underscore the potential for gender specific EPO action beyond erythropoiesis.—Zhang, Y., Rogers, H. M., Zhang, X., Noguchi, C. T. Sex difference in mouse metabolic response to erythropoietin.